Comparative Evaluation of the Effect of Implant Crown Materials on Implant Components and Bone Stress Distribution: A 3D Finite Element Analysis - Kimia Nokar; Faezeh Atri; Saied Nokar (International Journal of Dentistry)
Background. Choosing implant crown materials for restoration remains challenging in clinical practice. This study assesses the impact of all-ceramic restoration instead of porcelain-fused-to-metal (PFM) restoration on the stress distribution within implant components and the surrounding bone. Methods. Four 3D models of a mandibular second premolar were meticulously prepared. The study groups comprised zirconia, lithium disilicate, and zirconia lithium silicate monolithic ceramic crowns cemented onto a zirconia hybrid abutment. A PFM crown cemented onto a cementable abutment was chosen as the control group. A total vertical load of 583 N was applied to the occlusal contact areas. Stress distribution within the crown and implant components was analyzed using von Mises stress analysis. Principal stress analyses were employed to assess stress distribution in the peripheral bone. Results. The PFM model exhibited the highest von Mises stress values for both the implant (428.7 MPa) and crown (79.7 MPa) compared to the other models. The all-ceramic models displayed the highest maximum von Mises stress within the abutment, approximately 335 MPa, compared to the PFM model. von Mises stresses of the abutment and implant in the all-ceramic models were 69% higher and 20% lower, respectively, than those in the PFM model. Screw stresses were relatively consistent across all groups. Principal stresses in spongy bone and minimum principal stress in cortical bone were consistent across all models. Conclusions. All-ceramic restoration with a hybrid abutment, as opposed to traditional PFM restoration with a cementable abutment, does not adversely affect the implant and abutment screw and reduces crown stresses. Stresses within hybrid abutments were notably higher than those within cementable abutments. Spongy bone stresses remained unaffected by the type of crown or abutment.